(3JGQjN OeTb ddbdGfSs - (3CHi jYdj MeRI Hf CSO Hf Ydj Hf eMeO GdJejei GdOeTbj GdYejOs; (3MSjf Hf YHO Gddg GdcJHj Gdjefj, Gdjefj,J (B1152 (3g` s ((3eMeO Hf CHj HcQ Hf ESeGYjd GHf GdTjQLi GdehUdi s)
(3ChdgG (B:s
(3HYO GdOjHGLg agPG JGQjN eNJUQ ef JhGQjN GfJNHJgG eNdUkG eajOkG def WGdYg, efbhdI ef JhGQjN bOjeI s
(3BNQgG (B:s
(3gPG BNQ eG hLO ef ePjd GdJGQjN GdOeTbi hGdMeO ddg hMOI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B620s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B331 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B68 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs